Leadership Style and Competence Against State Apparatus Performance (Study at the Regional Secretariat Office of North Barito Regency) - Normila Normila; Hairudinor Hairudinor; Siswanto Rawali; Abdurrahman Abdurrahman (Wadah Inovasi Indonesia, 2021)
Leadership is a key factor in the success of an organization and management that directs the work of organizational members to achieve organizational goals. Measurement of organizational performance needs to be carried out in ensuring the understanding of the implementers and measuring achievement, ensuring the achievement of an agreed performance scheme, monitoring and evaluating performance with a comparison between work and implementation schemes, providing objective rewards and punishments for performance achievements that have been measured according to the measurement system has been agreed upon, making it a means of communication between employees and leaders in an effort to improve organizational performance, ensure that decisions are made objectively and reveal problems that occur. This study proves that have significant influence simultaneously and there is a partial significant influence leadership style and competence on the Performance of Administrative At the Regional Secretariat North Barito regency of 66.3% while the remaining 33.7% is influenced by other variables that are not included in this research model. Leaders should continuously provide high motivation so that work is done well, provide polite service to the community, provide what the community needs, work in accordance with leadership directions, and are willing to take full responsibility for the risks in every work done.